Um mecanismo baseado em sensibilidade à situação para otimizar a transmissão de dados de aplicações de sensoriamento urbano - Rolim, Carlos O.; Rossetto, Anubis G.; Leithardt, Valderi R. Q.; Borges, Guilherme A.; dos Santos, Tatiana F. M.; Souza, Adriano M.; Geyer, Claudio F. R. (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP); 2016: Anais do VIII Simpósio Brasileiro de Computação Ubíqua e Pervasiva, 2016)
One challenge in urban sensing applications is related to the transmission of data when network infrastructure is intermittent or unavailable. For such task, the Opportunistic Networks emerged as a promising alternative. The main problem in this context is how to improve messages routing between network nodes. Thus, this work presents a engine that employs situation awareness in conjunction with uncertainty treatment to overcome such limitation. The experiments demonstrate that the proposed engine was an acceptable performance and can be used as a basis for opportunistic data transmission in a urban sensing architecture called UrboSenti.